What does learning disability mean in the 'real world'?: re-evaluating conceptions and definitions of learning disability - Cluley, Victoria (2016)
What does learning disability mean in the ‘real world’? is a qualitative sociological thesis that explores the discursive resources used by different groups of people in relation to the term learning disability. Learning disability is a term that can mean different things to different people. It is also a term that can be seen from a variety of theoretical standpoints. Indeed, the term learning disability exists within a semantic tangle of definitions, concepts, colloquialisms, politics and attitudes that is fraught with historical, social and political tensions. While this is a feature of many terms, how learning disability is understood is of direct consequence to people with learning disabilities and the lives they live. This thesis aims to address this confusion and to work towards a re-evaluation of concepts and definitions of learning disability.